2018
DOI: 10.1002/cam4.1777
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase activation limits efficacy of Dasatinib in c‐Myc driven hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a deadly malignancy with limited treatment options. Recently, it was found that Dasatinib treatment led to synthetic lethality in c‐Myc high‐expressing human cancer cells due to inhibition of p‐Lyn. Overexpression of c‐Myc is frequently seen in human HCC. We investigated the sensitivity to Dasatinib in vitro using HCC cell lines and in vivo using c‐Myc mouse HCC model. We found that HCC cell line responsiveness to Dasatinib varied significantly. However, there was no correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…It was found that the IGF1 was involved in multiple cancer‐related pathways, such as proteoglycans, focal adhesion, and synaptic vesicle cycle. Focal adhesion had been confirmed to regulate cell proliferation, survival, migration, and invasion, which is overexpressed and/or activated in several cancers, including SCLC, colorectal cancer, and hepatocellular carcinoma . Accordingly, we infer that miR‐4784 may promote tumor cell growth and enhance cell invasion.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the IGF1 was involved in multiple cancer‐related pathways, such as proteoglycans, focal adhesion, and synaptic vesicle cycle. Focal adhesion had been confirmed to regulate cell proliferation, survival, migration, and invasion, which is overexpressed and/or activated in several cancers, including SCLC, colorectal cancer, and hepatocellular carcinoma . Accordingly, we infer that miR‐4784 may promote tumor cell growth and enhance cell invasion.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in vitro treatment with the combination of defactinib and dasatinib showed drug synergy in the DSRCT, ERMS, and ARMS cells. A similar synergistic effect was previously observed in neuroblastoma, acute lymphoblastic leukemia, and hepatocellular carcinoma (HCC) cells [ 21 , 27 , 32 ]. DSRCT, ERMS, and ARMS cells showed a higher level of drug synergy compared to ES cells.…”
Section: Discussionsupporting
confidence: 80%
“…FAK and Src inhibition, either as a single agent or as part of a combination treatment, has previously been shown to have preclinical effects in a variety of tumor types [ 21 , 25 37 ]. In this study, we specifically examined the effects of targeting the FAK-Src complex in pediatric and AYA sarcomas by examining pFAK and pSrc expressions in clinically derived tumor material of DSRCT, ES, ARMS, and ERMS patients and by examining in vitro and in vivo effects of the FAK inhibitor defactinib and the Abl/SFK inhibitor dasatinib combination treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7e ). Furthermore, we found that TGFβ1 induced PMEPA1 upregulation in c-MYC high expressed human HCC cell lines (Hep40 and HLF) 37 , but not in c-MYC low expressed human HCC cell lines (Huh7 and SNU475; Fig. 7f–h ), suggesting that PMEPA1 may be a target of TGFβ1 in the context of c-MYC HCC.…”
Section: Resultsmentioning
confidence: 86%